Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate, secondary battery and power-related equipment
By combining the porous carbon substrate of the carbon nanotubes with nanosilicon in situ, the powdering and shedding problems caused by volume changes in the silicon carbon anode material during lithium-embedded deliquefaction process are solved, and high cycle stability and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411721025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
The existing silicon-carbon negative electrode materials expand and shrink severely during the lithium-embedded deliquency process, resulting in the material being powdered and shedding, losing electrochemical properties. The porous carbon substrate has weak binding force with nano-silicon, poor conductivity, and poor circulation performance.
By synthesizing porous carbon in situ and growing carbon nanotubes in situ inside it, the volume expansion buffer space of nanosilicon particles is enhanced, the binding force between the substrate and nanosilicon is enhanced, and conductivity is improved. The specific steps include: mixing the water-soluble resin with the transition metal salt, performing reduction treatment after carbonization, then growing carbon nanotubes in a mixed atmosphere of carbon dioxide and acetylene, and finally undergoing silicon deposition and carbon coating.
It significantly improves the long cycle stability of silicon-carbon anode material, enhances the binding ability of nano-silicon particles to porous carbon substrates, improves electrochemical performance, and has high capacity and high first-term efficiency.
Smart Images

Figure BDA0005158040430000171 
Figure BDA0005158040430000181 
Figure BDA0005158040430000191
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and electrical equipment. Background Art
[0002] Silicon is currently the negative electrode material with the largest theoretical capacity, with a specific capacity of up to 4200mAh / g, which is much higher than the theoretical capacity of graphite (the theoretical capacity of graphite-based negative electrode materials is only 372mAh / g). Silicon has the advantages of low lithium insertion potential and low cost, and is expected to replace graphite as the next generation of lithium-ion battery negative electrode material. However, silicon as a negative electrode material is accompanied by severe volume expansion and contraction during the lithium insertion and de-lithiation process, which makes the material easy to pulverize and fall off the current collector and lose its electrochemical performance. Due to the structural stability of carbon materials, the volume change during the charge and discharge process is relatively small, and it has good cycle stability. In addition, it is similar to silicon in chemical properties, so silicon and carbon are often compounded to achieve the purpose of improving the volume expansion effect of silicon and improving its electrochemical stability. However, the porous carbon prepared by the prior art mostly adjusts the pore structure by physical or chemical activation methods, and the simple porous carbon substrate has weak binding force with nano-silicon and poor conductivity, so the negative electrode material prepared on this substrate has poor cycle performance.
[0003] In order to enhance the bonding force between the substrate and nano-silicon and improve the conductivity of the porous carbon substrate, other conductive materials (such as carbon nanotubes, graphene, and graphene sheets) are often introduced to compound with the substrate and adjust the pore structure. For example, the Chinese invention patent document with application publication number CN118458746A discloses an improved method for preparing silicon-carbon negative electrode materials, which is to immerse the porous substrate in a metal salt solution to load metal ions on the surface of the porous substrate, and use the metal ions as catalysts to catalyze the growth of carbon tubes, thereby achieving pore size adjustment and improved conductivity. However, in this method, the metal ions are loaded by vacuum impregnation, which inevitably causes metal salt solution to be stained on the surface of the substrate, making it difficult to control the carbon nanotubes to grow only inside the pores rather than on the surface; during the silane vapor deposition process, if a certain amount of carbon nanotubes grow on the surface of the substrate, nanosilicon particles are very likely to be deposited on the carbon nanotubes rather than enter the pores. At this time, the pore structure of the substrate has no restrictive effect on the nanosilicon particles deposited on the surface; and because a small amount of carbon tubes grow on the surface of the substrate, the specific surface area increases, making it difficult to achieve uniform coating of the carbon coating layer, which leads to the rupture of the coating layer during subsequent cycles, and the nanosilicon particles deposited on the carbon tubes react with the electrolyte, creating a safety hazard. Summary of the invention
[0004] In response to the above problems, the present invention discloses a method for preparing a silicon-carbon negative electrode material, its product and application. By in-situ synthesizing porous carbon and in-situ growing carbon nanotubes inside it, more buffer space is provided for the volume expansion of nano-silicon particles from the perspective of substrate preparation, thereby significantly improving the long-cycle stability of the silicon-carbon negative electrode material.
[0005] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising:
[0007] (S1) mixing a water-soluble resin and an aqueous solution of a transition metal salt uniformly, and drying to obtain a composite material of a resin-loaded metal salt;
[0008] (S2) carbonizing the resin-loaded metal salt composite material, and then reducing it to obtain a metal-loaded porous carbon;
[0009] (S3) placing the metal-loaded porous carbon in a mixed atmosphere of carbon dioxide and acetylene, in-situ growing carbon nanotubes inside the porous carbon, and obtaining modified porous carbon after acid washing;
[0010] (S4) Using the modified porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to obtain the silicon-carbon negative electrode material.
[0011] The present invention obtains metal-loaded porous carbon by mixing resin powder with transition metal salt solution and carbonizing. The transition metal salt has an activation effect, and can activate the carbon material during carbonization. Moreover, due to sufficient blending and drying with the resin, the transition metal salt can be dispersed inside the carbon material without remaining on the surface; thereby ensuring that the in-situ grown carbon nanotubes are also grown on the inner wall of the porous carbon rather than the outer surface. Furthermore, the porous carbon substrate and the nano silicon particles are combined through the in-situ grown carbon nanotubes, which effectively improves the combination ability of the two, and the carbon nanotubes provide good buffering and traction effects for the longitudinal expansion of the nano silicon particles.
[0012] In an optional embodiment, step (S1) includes at least one of the following features (1) to (3):
[0013] (1) The water-soluble resin is selected from one or more of a water-soluble epoxy resin, a water-soluble phenolic resin, a water-soluble urea-formaldehyde resin, and a water-soluble unsaturated polyester resin;
[0014] (2) The concentration of the transition metal salt aqueous solution is 0.001 to 1 mol / L; optionally, the concentration is 0.01 to 1 mol / L;
[0015] (3) The mass ratio of the water-soluble resin to the transition metal salt is 1:(0.1-10) based on the mass of the transition metal ions in the transition metal salt aqueous solution; optionally, the mass ratio of the two is 1:(1-5);
[0016] In an optional embodiment, in step (S1):
[0017] Optionally, the cations in the transition metal salt include but are not limited to one or more of Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Mn(II), and more optionally, Fe(III) and Co(II).
[0018] Optionally, the anions in the transition metal salt include but are not limited to soluble anions such as nitrate, chloride, sulfate, etc., and more optionally, are chloride ions.
[0019] In an optional embodiment, in step (S2), the specific temperature and time of the carbonization treatment are adaptively adjusted in the art according to the type of water-soluble resin used.
[0020] Optionally, the temperature of the carbonization treatment is 400-1000°C; more preferably, the temperature is 600-1000°C.
[0021] Optionally, the carbonization treatment time is 1 to 10 hours.
[0022] Optionally, the heating rate of the carbonization treatment is 0.5-10°C / min.
[0023] Optionally, the carbonization treatment is carried out in a rotary furnace, and the oxygen content in the furnace is controlled to be below 50 ppm and the furnace rotation speed is 0 to 10 rpm.
[0024] Optionally, the reduction treatment adopts conventional technical means in the art, and the transition metal salt is converted into transition metal particles after the reduction treatment;
[0025] Optionally, the reduction treatment is carried out in an atmosphere containing hydrogen;
[0026] Optionally, the reduction treatment is performed at a temperature of 400 to 1000° C. and for a time of 2 to 10 hours.
[0027] In an optional embodiment, a physical activation step is added in step (S2), that is, the porous carbon after carbonization is physically activated, and the physical activation comprises at least one of the following features (a) to (f):
[0028] (a) The physical activation is performed using an activating agent selected from water vapor, carbon dioxide and / or carbon monoxide;
[0029] (b) the flow rate of the activator is 0.1 to 20 kg / h, optionally, the flow rate is 1 to 12 kg / h;
[0030] (c) the mass ratio of the activator to the porous carbon after carbonization treatment is (0.1-2.0):1; optionally, the mass ratio of the two is (0.3-1.2):1;
[0031] (d) physical activation at a temperature of 600 to 1200° C.; alternatively, at a temperature of 650 to 1000° C.;
[0032] (e) physical activation, the pressure is 0.01 to 20 KPa; optionally, the pressure is 0.01 to 8 KPa;
[0033] (f) Physical activation, time is 0.5 to 15 hours.
[0034] Experiments have shown that the optionally added physical activation step can improve the pore structure of the porous carbon and further improve the long-cycle stability and reversible specific capacity of the final prepared silicon-carbon negative electrode material.
[0035] Further experiments found that different activators have different effects on the porous carbon pore structure, and thus have different effects on the electrochemical properties of the final prepared silicon-carbon negative electrode material. When the activator is selected from water vapor, the capacity of the final prepared silicon-carbon negative electrode material is significantly improved, and the cycle stability is slightly improved; when the activator is selected from carbon dioxide and / or carbon monoxide, the cycle stability of the final prepared silicon-carbon negative electrode material is significantly improved, and the capacity is slightly improved.
[0036] The reduction of the transition metal salt can be achieved during the physical activation, so there is no need for further reduction treatment after adding the physical activation step.
[0037] In an optional embodiment, step (S3) includes at least one of the following features (i) to (iv):
[0038] (1) The mixed atmosphere has a volume percentage of 3 to 20% acetylene, a volume percentage of 5 to 30% carbon dioxide, and the remainder being an inert gas;
[0039] (ii) the mixed atmosphere has a flow rate of 1 to 10 mol / h; optionally, a flow rate of 4 to 8 mol / h;
[0040] (iii) the in-situ growth is performed at a temperature of 400 to 600° C.;
[0041] (iv) The in situ growth time is 0.5 to 3.0 hours; optionally, the time is 0.5 to 2.5 hours; more optionally, the time is 1.0 to 2.5 hours.
[0042] Optionally, the pickling adopts an acid solution conventional in the art, such as a hydrochloric acid solution with a concentration of 0.01 to 0.1 M.
[0043] Optionally, the pickling may be performed once or multiple times.
[0044] In an optional embodiment, step (S4) comprises at least one of the following features (A) to (H):
[0045] (A) The silicon deposition is performed by placing the porous carbon substrate in a raw gas environment containing a silicon source gas to perform vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles;
[0046] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane;
[0047] (B) the raw material gas containing silicon source gas has a flow rate of 1 to 50 L / h; optionally, 5 to 20 L / h;
[0048] (C) the raw material gas containing the silicon source gas contains an inert gas, which accounts for 1 to 30% by volume; the inert atmosphere is used as a carrier gas, and optionally, is selected from an inert gas such as argon and helium;
[0049] (D) the silicon deposition is carried out at a temperature of 300 to 600° C. for a time of 1 to 20 hours;
[0050] (E) The carbon coating comprises placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material;
[0051] (F) the carbon source gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; optionally, the C1-C4 alkanes are selected from methane, ethane, propane, and butane; optionally, the C2-C4 alkenes are selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkynes are selected from acetylene, propyne, and butyne;
[0052] (G) the raw gas containing the carbon source gas has a flow rate of 1 to 10 L / h;
[0053] (H) The carbon coating is carried out at a temperature of 400 to 600° C. for a time of 1 to 10 hours.
[0054] In a second aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method.
[0055] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned silicon-carbon negative electrode material.
[0056] In a fourth aspect, the present invention further provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0057] In a fifth aspect, the present invention further provides an electrical device, comprising the above-mentioned secondary battery.
[0058] Compared with the prior art, the present invention has the following beneficial results:
[0059] The invention discloses a method for preparing a silicon-carbon negative electrode material. Resin powder is mixed with a transition metal salt solution and carbonized to obtain metal-loaded porous carbon. The transition metal salt has an activation effect and can activate the carbon material during carbonization. Due to the full mixing of the resin and the metal salt, the metal is evenly dispersed. Then, during the carbonization process, the places where there is metal are activated to form holes and are sunken. There is no metal in the places where there is no activation. This ensures that the carbon nanotubes grown in situ are also grown on the inner wall of the porous carbon rather than the outer surface.
[0060] Furthermore, physical activation treatment of the carbonized porous carbon can improve the pore structure of the porous carbon and further improve the long-cycle stability and reversible specific capacity of the final prepared silicon-carbon negative electrode material; different physical activators have different effects on the above parameters, which can be adjusted according to specific customer needs.
[0061] The porous carbon substrate and nano-silicon particles prepared in situ in the present invention are combined through the in situ grown carbon nanotubes, which effectively improves the binding ability between the two. The carbon nanotubes provide good buffering and traction effects for the longitudinal expansion of the nano-silicon particles. The prepared silicon-carbon negative electrode material has excellent long-cycle stability and has both high capacity and high initial efficiency. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0063] In a first aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material, which specifically comprises:
[0064] (S1) mixing a water-soluble resin and an aqueous solution of a transition metal salt uniformly, and drying to obtain a composite material of a resin-loaded metal salt;
[0065] (S2) carbonizing the resin-loaded metal salt composite material, and then reducing it to obtain a metal-loaded porous carbon;
[0066] (S3) placing the metal-loaded porous carbon in a mixed atmosphere of carbon dioxide and acetylene, in-situ growing carbon nanotubes inside the porous carbon, and obtaining modified porous carbon after acid washing;
[0067] (S4) Using the modified porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to obtain the silicon-carbon negative electrode material.
[0068] The present invention obtains metal-loaded porous carbon by mixing resin powder with transition metal salt solution and carbonizing. The transition metal salt has an activation effect, and can activate the carbon material during carbonization. Moreover, due to sufficient blending and drying with the resin, the transition metal salt can be dispersed inside the carbon material without remaining on the surface; thereby ensuring that the in-situ grown carbon nanotubes are also grown on the inner wall of the porous carbon rather than the outer surface. Furthermore, the porous carbon substrate and the nano silicon particles are combined through the in-situ grown carbon nanotubes, which effectively improves the combination ability of the two, and the carbon nanotubes provide good buffering and traction effects for the longitudinal expansion of the nano silicon particles.
[0069] In an optional embodiment, step (S1) includes at least one of the following features (1) to (3):
[0070] (1) The water-soluble resin is selected from one or more of water-soluble epoxy resin, water-soluble phenolic resin, water-soluble urea-formaldehyde resin and water-soluble unsaturated polyester resin.
[0071] (2) The concentration of the aqueous transition metal salt solution is 0.001 to 1 mol / L; specifically, it can be 0.001 mol / L, 0.005 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L or any value within the above range; optionally, the concentration is 0.01 to 1 mol / L.
[0072] (3) The mass ratio of the water-soluble resin to the transition metal salt is 1:(0.1-10) based on the mass of the transition metal ions in the transition metal salt aqueous solution; specifically, it can be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any ratio within the above range; optionally, the mass ratio of the two is 1:(1-5).
[0073] In an optional embodiment, in step (S1):
[0074] Optionally, the cations in the transition metal salt include but are not limited to one or more of Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Mn(II), and more optionally, Fe(III) and Co(II).
[0075] Optionally, the anions in the transition metal salt include but are not limited to soluble anions such as nitrate, chloride, sulfate, etc., and more optionally, are chloride ions.
[0076] In an optional embodiment, in step (S2), the specific temperature and time of the carbonization treatment are adaptively adjusted in the art according to the type of water-soluble resin used.
[0077] Optionally, the temperature of the carbonization treatment is 400-1000°C, specifically 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or any value within the above range; more optionally, the temperature is 600-1000°C.
[0078] Optionally, the carbonization treatment time is 1 to 10 h, specifically 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the above range.
[0079] Optionally, the heating rate of the carbonization treatment is 0.5-10°C / min, specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the above range.
[0080] Optionally, the carbonization treatment is carried out in a rotary furnace, and the oxygen content in the furnace is controlled to be below 50 ppm and the furnace rotation speed is 0 to 10 rpm.
[0081] Optionally, the reduction treatment adopts conventional technical means in the art, and the transition metal salt is converted into transition metal particles after the reduction treatment;
[0082] Optionally, the reduction treatment is carried out in a hydrogen-containing atmosphere; the raw gas includes hydrogen and an inert atmosphere, and the volume proportion of hydrogen is 10 to 90 vol%, specifically 10 vol%, 15 vol%, 20 vol%, 25 vol%, 30 vol%, 35 vol%, 40 vol%, 45 vol%, 50 vol%, 55 vol%, 60 vol%, 65 vol%, 70 vol%, 75 vol%, 80 vol%, 75 vol%, 90 vol% or any value within the above range; more optionally, it is 20 to 50 vol%.
[0083] Optionally, the temperature of the reduction treatment is 400-1000°C, specifically 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or any value within the above range.
[0084] Optionally, the reduction treatment time is 2 to 10 h, specifically 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the above range.
[0085] In an optional embodiment, a physical activation step is added in step (S2), that is, the porous carbon after carbonization is physically activated, and the physical activation comprises at least one of the following features (a) to (f):
[0086] (a) The physical activation is performed using an activating agent selected from water vapor, carbon dioxide and / or carbon monoxide;
[0087] (b) the flow rate of the activator is 0.1-20 kg / h, specifically 0.1 kg / h, 0.5 kg / h, 1 kg / h, 2 kg / h, 3 kg / h, 4 kg / h, 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h, 10 kg / h, 11 kg / h, 12 kg / h, 13 kg / h, 14 kg / h, 15 kg / h, 16 kg / h, 17 kg / h, 18 kg / h, 19 kg / h, 20 kg / h or any value within the above range; optionally, the flow rate is 1-12 kg / h;
[0088] (c) the mass ratio of the activator to the porous carbon after carbonization treatment is (0.1-2.0):1; specifically, it can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1 or any ratio within the above range; optionally, the mass ratio of the two is (0.3-1.2):1;
[0089] (d) physical activation at a temperature of 600 to 1200° C., specifically 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., 1200° C. or any value within the above range; optionally, the temperature is 650 to 1000° C.;
[0090] (e) physical activation, the pressure is 0.01-20 KPa, specifically 0.01 KPa, 0.05 KPa, 0.1 KPa, 0.5 KPa, 1 KPa, 2 KPa, 3 KPa, 4 KPa, 5 KPa, 6 KPa, 7 KPa, 8 KPa, 9 KPa, 10 KPa, 11 KPa, 12 KPa, 13 KPa, 14 KPa, 15 KPa, 16 KPa, 17 KPa, 18 KPa, 19 KPa, 20 KPa or any value within the above range; optionally, the pressure is 0.01-8 KPa;
[0091] (f) physical activation, the time is 0.5 to 15 h, specifically 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value within the above range.
[0092] Experiments have shown that the optionally added physical activation step can improve the pore structure of the porous carbon and further improve the long-cycle stability of the final prepared silicon-carbon negative electrode material.
[0093] Further experiments found that different activators have different effects on the porous carbon pore structure, and thus have different effects on the electrochemical properties of the final prepared silicon-carbon negative electrode material. When the activator is selected from water vapor, the capacity of the final prepared silicon-carbon negative electrode material is significantly improved, and the cycle stability is slightly improved; when the activator is selected from carbon dioxide and / or carbon monoxide, the cycle stability of the final prepared silicon-carbon negative electrode material is significantly improved, and the capacity is slightly improved.
[0094] The reduction of the transition metal salt can be achieved during the physical activation, so there is no need for further reduction treatment after adding the physical activation step.
[0095] In an optional embodiment, step (S3) includes at least one of the following features (i) to (iv):
[0096] (i) The volume percentage of acetylene in the mixed atmosphere is 3-20%, specifically 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value within the above range;
[0097] The volume percentage of carbon dioxide in the mixed atmosphere is 5-30%, specifically 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 25%, 30% or any value within the above range;
[0098] The mixed atmosphere has the balance of inert gas; the inert gas is selected from common inert gases such as argon and helium.
[0099] (ii) the mixed atmosphere has a flow rate of 1 to 10 mol / h; specifically, it may be 1 mol / h, 2 mol / h, 3 mol / h, 4 mol / h, 5 mol / h, 6 mol / h, 7 mol / h, 8 mol / h, 9 mol / h, 10 mol / h or any value within the above range; optionally, the flow rate is 4 to 8 mol / h;
[0100] (iii) the in-situ growth temperature is 400-600°C; specifically, it can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or any value within the above range;
[0101] (IV) The in situ growth time is 0.5 to 3.0 h; specifically, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3.0 h or any value within the above range; optionally, the time is 0.5 to 2.5 h; more optionally, it is 1.0 to 2.5 h.
[0102] Optionally, the pickling uses a conventional acidic solution in the art, such as a hydrochloric acid solution with a concentration of 0.01 to 0.1 M; specifically, the concentration of the hydrochloric acid solution is 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M or any value within the above range.
[0103] Optionally, the pickling may be performed once or multiple times.
[0104] In an optional embodiment, step (S4) comprises at least one of the following features (A) to (H):
[0105] (A) The silicon deposition is performed by placing the porous carbon substrate in a raw gas environment containing a silicon source gas to perform vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles;
[0106] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane;
[0107] (B) the raw material gas containing silicon source gas has a flow rate of 1 to 50 L / h; specifically, it can be 1 L / h, 2 L / h, 3 L / h, 4 L / h, 5 L / h, 8 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h, 30 L / h, 35 L / h, 40 L / h, 45 L / h, 50 L / h or any value within the above range; optionally, it is 5 to 20 L / h;
[0108] (C) the raw material gas containing silicon source gas contains inert gas, the volume percentage of which is 1-30%; specifically, it can be 1%, 2%, 3%, 4%, 5%, 8%, 10%, 15%, 20%, 25%, 30% or any value within the above range; the inert atmosphere is used as a carrier gas, and optionally, is selected from inert gases such as argon and helium;
[0109] (D) The silicon deposition temperature is 300-600° C., specifically 300° C., 350° C., 400° C., 450° C., 500° C., 550° C., 600° C. or any value within the above range; too high a temperature for silicon deposition will lead to excessive increase in the size of silicon crystal domains, which is not conducive to improving the cycle performance of the negative electrode material;
[0110] The silicon deposition time is 1 to 20 hours; specifically, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours or any value within the above range. The silicon deposition time must match the silicon deposition temperature. If the silicon deposition temperature is high, the deposition time is short; if the silicon deposition temperature is low, the deposition time is appropriately extended.
[0111] (E) The carbon coating comprises placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material;
[0112] (F) the carbon source gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; optionally, the C1-C4 alkanes are selected from methane, ethane, propane, and butane; optionally, the C2-C4 alkenes are selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkynes are selected from acetylene, propyne, and butyne;
[0113] (G) The raw gas containing the carbon source gas has a flow rate of 1 to 10 L / h; specifically, it can be 1 L / h, 2 L / h, 3 L / h, 4 L / h, 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h, 10 L / h or any value within the above range;
[0114] (H) The carbon coating temperature is 400-600°C, specifically 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C or any value within the above range; if the carbon coating temperature is too high, the particle size of the silicon domains deposited in the previous step will increase, and if the temperature is too low, the conductivity of the deposited carbon layer will deteriorate.
[0115] The carbon coating time is 1 to 10 hours; specifically, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or any value within the above range. The carbon coating time must match the carbon coating temperature. If the carbon coating temperature is high, the deposition time is short; if the carbon coating temperature is low, the deposition time is appropriately extended.
[0116] In a second aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method, wherein the silicon-carbon negative electrode material has a low specific surface area and a low resistivity.
[0117] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned silicon-carbon negative electrode material.
[0118] In a fourth aspect, the present invention further provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0119] In a fifth aspect, the present invention further provides an electrical device, comprising the above-mentioned secondary battery, which has excellent cycle stability and has both high reversible specific capacity and first coulombic efficiency.
[0120] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0121] Example 1
[0122] (S1) 20 kg of water-soluble phenolic resin (Jinan Dahui Chemical Technology Co., Ltd., model PF-2123) was dissolved in a 0.05 mol / L FeCl3 aqueous solution (the mass ratio of resin to iron salt was 1:2.5), and stirred for 10 h. After drying, a resin composite containing Fe(NO3)3 was obtained.
[0123] (S2) placing the composite in a rotary kiln, controlling the rotation speed of the kiln to 5 rpm after removing oxygen, heating the kiln to 800° C. at 5° C. / min and keeping the temperature for 4 h for carbonization treatment; after the carbonization treatment, introducing a mixed gas consisting of H2 (30 vol%) and nitrogen (70 vol%), performing a reduction treatment at 600° C. for 4 h to obtain a porous carbon loaded with metal;
[0124] After testing, the specific surface area of porous carbon is 674m 2 / g, average pore diameter of 5.01nm, pore volume of 0.63cm3 / g.
[0125] (S3) placing the porous carbon obtained in step S2 in a CVD furnace, introducing CO2 to remove excess oxygen in advance, introducing a mixed gas of 20% CO2 and 8% C2H2 gas (the rest is nitrogen) in volume percentage into the furnace, the mixed gas flow rate is 6 mol / h, the reaction temperature is 500°C, the reaction time is 1 h, and then the crude product is acid-washed with a 0.1 M hydrochloric acid aqueous solution to obtain a modified porous carbon with in-situ grown carbon nanotubes;
[0126] (S4) Turn off carbon dioxide and acetylene, adjust the temperature of the CVD furnace to 600°C, and introduce a mixed gas of 70 vol% monosilane and 30 vol% nitrogen into the deposition furnace at a total flow rate of 10 L / h, and continue to ventilate for 8 hours; after the silicon deposition is completed, introduce acetylene at a flow rate of 5 L / h for high-temperature carbon coating, continue to ventilate for 2 hours and then cool to room temperature. After the material is broken up, screened, demagnetized, etc., a silicon-carbon negative electrode material is obtained; the theoretical mass of the carbon coating layer is controlled to account for 3wt% of the mass of the finally prepared silicon-carbon negative electrode material.
[0127] Example 2
[0128] The preparation process is basically the same as that of Example 1, except that in step (S2), the porous carbon obtained after carbonization treatment is physically activated without reduction treatment, specifically:
[0129] 100 g of porous carbon after carbonization treatment was placed in an activation furnace, the temperature in the furnace was adjusted to 750°C, the furnace was evacuated, and water vapor was introduced at a flow rate of 4 kg / h for activation treatment. The mass ratio of activation gas water vapor to porous carbon was 0.8:1, and the porous carbon material after activation treatment was obtained.
[0130] After testing, the parameters of the porous carbon after activation treatment are as follows: the specific surface area is 730m 2 / g, the average pore diameter is 5.11nm, and the pore volume is 0.93cm 3 / g.
[0131] Example 3
[0132] The preparation process is basically the same as that of Example 2, with the only difference being that during the physical activation in step (S2), the mass ratio of the activation gas water vapor to the porous carbon substrate is replaced with 1.2:1.
[0133] Example 4
[0134] The preparation process is basically the same as that of Example 2, with the only difference being that during the physical activation in step (S2), the mass ratio of the activation gas water vapor to the porous carbon substrate is replaced with 0.4:1.
[0135] Example 5
[0136] The preparation process is basically the same as that in Example 2, the only difference is that during physical activation in step (S2), the activation gas is replaced by carbon dioxide, the pressure in the furnace is controlled to be 5Kpa, the flow rate is 8kg / h, and the mass ratio of the activation gas carbon dioxide to the porous carbon is 1:1.
[0137] After testing, the parameters of the porous carbon after activation treatment are as follows: the specific surface area is 1649m 2 / g, average pore diameter is 3.57nm, pore volume is 0.99cm 3 / g.
[0138] Example 6
[0139] The preparation process is substantially the same as that of Example 2, except that the reaction time is replaced with 2.5 h during the in-situ growth of carbon nanotubes in step (S3).
[0140] Example 7
[0141] The preparation process is substantially the same as that of Example 2, except that the reaction time is replaced with 0.5 h during the in-situ growth of carbon nanotubes in step (S3).
[0142] Example 8
[0143] The preparation process is basically the same as that of Example 1, except that in step (S1), the amount of FeCl3 aqueous solution added is adjusted and the mass ratio of resin to iron salt is replaced to 1:5.
[0144] After testing, the specific surface area of the porous carbon obtained after carbonization treatment is 1823m 2 / g, the average pore diameter is 3.2nm, and the pore volume is 0.91cm 3 / g.
[0145] Example 9
[0146] The preparation process is basically the same as that of Example 8, except that in step (S2), the porous carbon obtained after the carbonization treatment is further physically activated, specifically:
[0147] 100 g of porous carbon after carbonization treatment was placed in an activation furnace, the temperature in the furnace was adjusted to 750°C, the furnace was evacuated, and water vapor was introduced at a flow rate of 4 kg / h for activation treatment. The mass ratio of activation gas water vapor to porous carbon was 0.3:1, and the porous carbon material after activation treatment was obtained.
[0148] After testing, the specific surface area of the activated porous carbon is 1865m 2 / g, average pore diameter of 3.4nm, pore volume of 1.08cm 3 / g.
[0149] Example 10
[0150] The preparation process is basically the same as that of Example 8, except that in step (S2), the porous carbon obtained after the carbonization treatment is further physically activated, specifically:
[0151] 100g of carbonized porous carbon was placed in an activation furnace, the temperature in the furnace was adjusted to 750°C, the activation gas was replaced with carbon dioxide, the pressure in the furnace was controlled to be 5Kpa, the flow rate was 8kg / h, and the mass ratio of the activated gas carbon dioxide to the porous carbon was 0.5:1, to obtain the activated porous carbon material.
[0152] After testing, the specific surface area of the activated porous carbon is 2011m 2 / g, average pore diameter is 3.02nm, pore volume is 1.12cm 3 / g.
[0153] Comparative Example 1
[0154] The basic parameters are selected as the specific surface area of 1800m 2 / g, average pore diameter of 5.25nm, pore volume of 0.92cm 3 / g of porous carbon, 100g of the above porous carbon was immersed in 0.01M ferric chloride aqueous solution at 50°C, and after immersion for 24h, the porous carbon loaded with metal salt was obtained; it was then placed in a hydrogen atmosphere (H2 (30vol%) and nitrogen (70vol%)) for reduction treatment, and treated at 600°C for 4h to obtain the porous carbon loaded with iron.
[0155] The steps of in-situ growth of carbon nanotubes, silicon deposition and carbon coating are exactly the same as steps (S3) to (S4) in Example 8.
[0156] Comparative Example 2
[0157] The preparation process is basically the same as that of Example 2, except that the carbon nanotubes are not generated in situ, that is, the porous carbon obtained after carbonization and physical activation in step (S3) is used as a substrate to directly perform silicon deposition and carbon coating processes.
[0158] Comparative Example 3
[0159] The preparation process is basically the same as that of Example 8, except that the carbon nanotubes are not generated in situ, that is, the porous carbon obtained after carbonization in step (S3) is used as a substrate to directly perform silicon deposition and carbon coating processes.
[0160] Table 1 shows the performance parameters of the silicon-carbon negative electrode materials prepared in each embodiment and comparative example, wherein the particle size test is performed by Malvern 3000 test, the powder resistance is measured by a semiconductor powder resistivity tester (30 MPa four-probe V1.4), the tap density is measured by a tap density meter, and the specific surface area is tested by Micromeritics 3020.
[0161] Table 1
[0162]
[0163]
[0164] Application examples:
[0165] Batteries were assembled using the products prepared in each embodiment and each comparative example as negative electrode materials.
[0166] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.
[0167] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the products prepared in each embodiment and each comparative example were added as negative electrode active materials and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).
[0168] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.
[0169] (3) Assembly of lithium-ion batteries
[0170] Using PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an aluminum plastic shell package, and dried at 100°C under a relative vacuum pressure of -0.95×105Pa until the moisture content is less than 100ppm. The electrolyte is injected into the dried bare battery cell, wherein the electrolyte is composed of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and the package, static, formation (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaping, and capacity testing (capacity separation) are performed to make a soft-pack liquid lithium-ion battery.
[0171] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.
[0172] The battery cycle performance is tested on the Xinwei equipment, specifically:
[0173] At 25°C, first discharge at 0.1C to 0.005V, then discharge at 0.08C to 0.001V, discharge at 0.05C to 0.001V, discharge at 0.02C to 0.001V, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 300 times in the above manner, record the charge and discharge capacity after 300 times, and calculate the capacity retention rate after 300 cycles. The test and calculation process of the capacity retention rate after 600 cycles adopt the same method. The specific test / calculation results are shown in Table 2 below.
[0174] Table 2
[0175]
[0176]
[0177] According to the data of Example 1 in Table 2, the silicon-carbon negative electrode material prepared by the method of the present invention has excellent cycle stability, but the porous carbon prepared only by the activation of transition metal salts has fewer pores and lower pore volume, resulting in less silicon deposition and lower reversible specific capacity.
[0178] By comparing Example 1 with Example 2 and Example 5, it can be found that when the physical activation step is added after the carbonization treatment, the pore structure of the porous carbon is further activated, the pore volume is increased, and the reversible specific capacity of the silicon-carbon negative electrode material finally prepared is improved. The silicon-carbon negative electrode material prepared with water vapor as an activator has a significant improvement in reversible specific capacity while maintaining high cycle stability; the reversible specific capacity of the silicon-carbon negative electrode material prepared with carbon dioxide as an activator is slightly improved, and the capacity retention rate is further improved. By comparing the data of Examples 8 to 10, the same change trend as above can be obtained.
[0179] By comparing Examples 2 to 4, it can be found that when the amount of activator is large, the reversible specific capacity of the prepared silicon-carbon negative electrode material is large, but the cycle stability is reduced; conversely, the reversible specific capacity of the prepared silicon-carbon negative electrode material is small, but the cycle stability is improved.
[0180] By comparing Examples 2, 6 and 7, it can be found that adjusting the in-situ growth time of carbon nanotubes also affects the electrochemical performance of the prepared silicon-carbon negative electrode material.
[0181] By comparing Examples 2 and 8, it can be found that compared with the silicon-carbon negative electrode material prepared only by the activation of transition metal salts in Example 8, the porous carbon prepared after two activation treatments of activation by transition metal salts combined with physical activation in Example 2 has a better pore structure, and the finally prepared silicon-carbon negative electrode material has higher long-cycle stability.
[0182] By comparing Example 8 with Comparative Example 1, it can be found that since the carbon nanotubes in Comparative Example 1 grow in situ inside and on the surface of the porous carbon (as long as the position impregnated with the metal salt can grow), its long cycle stability is poor. However, the silicon-carbon negative electrode material prepared by the process of the present invention can ensure that all carbon nanotubes grow in situ inside the porous carbon, and has excellent long cycle stability.
[0183] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: include: (S1) mixing a water-soluble resin and an aqueous solution of a transition metal salt uniformly, and drying to obtain a composite material of a resin-loaded metal salt; (S2) carbonizing the resin-loaded metal salt composite material, and then reducing it to obtain a metal-loaded porous carbon; (S3) placing the metal-loaded porous carbon in a mixed atmosphere of carbon dioxide and acetylene, in-situ growing carbon nanotubes inside the porous carbon, and obtaining modified porous carbon after acid washing; (S4) Using the modified porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to obtain the silicon-carbon negative electrode material.
2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S1), at least one of the following features (1) to (3) is included: (1) The water-soluble resin is selected from one or more of a water-soluble epoxy resin, a water-soluble phenolic resin, a water-soluble urea-formaldehyde resin, and a water-soluble unsaturated polyester resin; (2) The concentration of the transition metal salt aqueous solution is 0.001 to 1 mol / L; (3) The mass ratio of the water-soluble resin to the transition metal salt is 1:(0.1-10) based on the mass of the transition metal ions in the transition metal salt aqueous solution.
3. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S2), the carbonization treatment is carried out at a temperature of 400 to 1000° C. for a time of 1 to 10 hours.
4. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S2), the porous carbon after carbonization is physically activated, and the physical activation comprises at least one of the following features (a) to (f): (a) The physical activation is performed using an activating agent selected from water vapor, carbon dioxide and / or carbon monoxide; (b) the flow rate of the activator is 0.1 to 20 kg / h; (c) The mass ratio of the activator to the porous carbon after carbonization treatment is (0.1-2.0):1; (d) physical activation, the temperature is 600-1200°C; (e) Physical activation, pressure is 0.01 ~ 20Kpa; (f) Physical activation, time is 0.5 to 15 hours.
5. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S3), at least one of the following features (i) to (iv) is included: (1) The mixed atmosphere has a volume percentage of 3 to 20% acetylene, a volume percentage of 5 to 30% carbon dioxide, and the remainder being an inert gas; (ii) the mixed atmosphere has a flow rate of 1 to 10 mol / h; (iii) the in-situ growth is performed at a temperature of 400 to 600° C.; (iv) The in situ growth time is 0.5 to 3.0 hours.
6. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S4), at least one of the following features (A) to (H) is included: (A) The silicon deposition is performed by placing the porous carbon substrate in a raw gas environment containing a silicon source gas to perform vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles; (B) the raw material gas containing silicon source gas has a flow rate of 1 to 50 L / h; (C) the raw material gas containing silicon source gas contains inert gas, accounting for 1 to 30% by volume; (D) the silicon deposition is carried out at a temperature of 300 to 600° C. for a time of 1 to 20 hours; (E) The carbon coating comprises placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material; (F) the carbon source gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; (G) the raw gas containing the carbon source gas has a flow rate of 1 to 10 L / h; (H) The carbon coating is carried out at a temperature of 400 to 600° C. for a time of 1 to 10 hours.
7. A silicon-carbon negative electrode material prepared by the method according to any one of claims 1 to 6.
8. A negative electrode plate, characterized in that: Comprising the silicon-carbon negative electrode material as described in claim 7.
9. A secondary battery, characterized in that: Comprising the negative electrode sheet as described in claim 8.
10. An electrical device comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Preparation method of improved silicon-carbon negative electrode material
CN118458746A
Cited By
Spherical porous carbon as well as preparation method and application thereof
CN119976806A
Graphene-doped porous carbon material, preparation method and application thereof, silicon-carbon negative electrode material and battery
CN121107409A